A morphological study with clinical, pathological, and immunohistochemical characterization of non-Hodgkin lymphoma - Mohit Kumar; Jayaprakash C S; Athira K P (Medical Laboratory Journal)
Background: Non-Hodgkin lymphoma (NHL) represents a heterogeneous group of lymphoproliferative malignancies with unique presentation and treatment response. This study was intended to assess the histomorphology of non-Hodgkin lymphoma subtypes and correlate with clinicopathological and immunohistochemical findings. Methods: This retrospective study was conducted on all specimens diagnosed as NHL by histopathological analysis, with immunohistochemical correlation in the pathology department, for two years. Clinical details such as age, gender, site of the lesion, and Nodal / extranodal presentation were recorded. Histopathological analysis was performed, and Immunohistochemical (IHC) reports were obtained. Further histopathological findings were correlated with IHC results. Statistical analysis was done based on the frequency distribution. Results: This study includes 48 cases. Most cases are 61 to 70 years old, with a male predominance (56.25 %). The most common clinical diagnosis was lymphoma (79.17 %).  Most of the lesions were of lymph nodal origin (60.42 %). The cervical group (35.42 %) is the most common lymph node affected, followed by the axillary nodes. The most common extranodal sites are the retroperitoneum and stomach. On histopathological evaluation, the most common diagnosis was NHL (68.75 %) without further subtyping. Among cases where subtyping was done, the most common lesion were follicular lymphoma and diffuse large B-cell lymphoma (DLBCL). On IHC evaluation, B cell neoplasms (85.42%) were common compared to T cell neoplasms (14.58 %). The most common subtype was DLBCL (52.08 %), followed by follicular lymphoma (16.67 %). Conclusion: Our study found diffuse large B cell lymphoma (DLBCL) as the most common type of Non-Hodgkin’s Lymphoma. Cervical lymph nodes were found to be the most common site of involvement. But the involvement of rare sites like the testis and palate was also found. Hence the probability of NHL in these rare sites should always be considered.